Trading off fiscal budget adherence and child protection - Cavalca, Petra Gram; Ejrnæs, Mette; Gørtz, Mette (PLOS ONE, 2022)
Many countries delegate a substantial part of social service decisions to local administrative levels, while federal laws provide the overall framework for service levels. Strict regulations to reduce budget overruns may however leave local governments with a potential trade-off between adhering to fiscal budgets and supplying critical welfare services as e.g. programs to protect vulnerable children. We investigate if budgetary constraints influence child protection decisions using high-quality register data. We show that the introduction of fiscal sanctions to improve budget adherence contributed to a sharp decline in budget overruns on child protective services by reducing the number of children in out-of-home care. Our results further show that monthly variation in budget adherence within a fiscal year affects the probability of a placement in out-of-home care for children in need of help towards the end of a fiscal year. We estimate that a budget overrun of 10 percentage points by mid-year leads to a 1.2 percent reduction in the number of children in care over the remaining part of the fiscal year. Municipalities reduced child protection expenditure by choosing cheaper types of care and ending placement for children in out-of-home care, particularly for children turning 18. Our paper contributes to the literature on fiscal federalism by documenting the trade-off between managing public expenditure and providing safety and equal opportunity for vulnerable children. We thus highlight that enforcing strict budget adherence may be in conflict with social policy goals. Our results raise an important discussion about centralization versus delegation of critical public services.